Barrier red algae fiber, preparation method thereof, barrier coated paper comprising barrier red algae fiber and barrier sheet

By adopting elliptical red algae fibers and performing specific preparation treatments, the problem of insufficient anti-oxygen penetration and dehydration properties of the barrier paper in the prior art is solved, and more efficient barrier properties and better environmental protection characteristics are achieved.

CN119790200APending Publication Date: 2025-04-08ALAMI MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037129.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-14
Filing Date
2023-09-14
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, barrier paper lacks biodegradable materials with excellent anti-oxygen permeability and dehydration properties, and it is difficult to replace petrochemical raw materials.

Method used

The oval red algae fibers were prepared by specific preparation methods, including sulfuric acid treatment and bleaching steps, and were used to block coated paper and blocking sheets.

Benefits of technology

It achieves better anti-oxygen permeability and dehydration properties than traditional nanocellulose, providing an environmentally friendly, degradable barrier material solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790200A_ABST
    Figure CN119790200A_ABST
Patent Text Reader

Abstract

The present invention relates to a barrier red algae fiber, a method for preparing the same, and a barrier coated paper and a barrier sheet comprising the same, the barrier coated paper according to the present invention having an oxygen permeation prevention property, a better dehydration effect during a coating process than conventional nanocellulose derived from wood, and a biodegradability property, and thus being environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to barrier red algae fiber, and more particularly to barrier red algae fiber, a preparation method thereof, barrier coated paper and barrier sheet comprising the same. Background Art

[0002] Generally, "paper" is made of pulp fibers entangled together, and there are many spaces, so oxygen or water vapor can easily pass through. In other words, it does not have barrier properties that can inhibit the penetration of moisture, oxygen and other substances flowing in from the outside into the inside. Therefore, most packaging papers are treated with barrier coatings, and the most widely used method is mainly lamination of polyethylene (PE), and latex coating is also considered. These materials are excellent in imparting moisture resistance, but because they are petrochemical carbon compounds, they are difficult to biodegrade and are not environmentally friendly. Therefore, there is an urgent need to discover new natural raw materials that can replace petrochemical raw materials and expand their uses.

[0003] Therefore, efforts have been made to obtain barrier properties from environmentally friendly raw materials using petrochemical raw materials such as polyethylene. Cellulose, which is the most representative environmentally friendly raw material, is divided into nanometer (nm) scale cellulose nanofibrils (CNF) and is considered as a candidate group to replace petrochemical raw materials and enhance the barrier properties of packaging materials. Cellulose nanofibrils are sustainable, biodegradable natural organic polymers, usually with a width of less than 100nm and a length of several μm. As is known to all, the aspect ratio of such cellulose nanofibers is very large, the specific surface area is high, and the strength properties are excellent. In addition, cellulose nanofibers are easily prepared into films through strong hydrogen bonds formed between nanocellulose during drying. Membrane-like cellulose nanofibers can impart strong barrier properties to oxygen and liquids, so it is expected that they can be used as environmentally friendly barrier properties in the field of packaging paper. However, the nanocellulose used so far is nanocellulose derived from wood, which has poor dehydration properties. Therefore, it is urgent to explore biodegradable barrier raw materials with better dehydration properties and oxygen permeation resistance.

[0004] On the other hand, red algae contain red algae and cyanophytin in addition to chlorophyll. They are red or purple seaweeds that live in water deeper than other algae. They are relatively small in size and have more than 4,000 species, which are very diverse. Red algae have a wider range of habitats than green algae and brown algae, growing from shallow water to deep water where light shines. Red algae include many fibers called root-like filaments in seaweed. These fibers have a diameter of several microns and are formed by almost a fixed size in all red algae. In addition, the whiteness and opacity of red algae fibers are excellent, and the bonding ability between red algae fibers is also excellent. The crystallinity of red algae fibers is similar to that of cellulose fibers. In particular, the thermal properties of bleached red algae fibers are superior to those of cellulose fibers. Red algae include laver, agar, chicken feather vegetables, chicken foot vegetables, gracilaria, long-branched sand vegetables, three-forked celestial vegetables, Boden celestial vegetables, pseudo-thick membrane algae, sea rope noodles, linear soft spiny algae, hooked vegetables and centipede algae. The internal gel extracts of red algae are all used as food additives, health products, agar materials, etc.

[0005] As barrier film related technologies, Korean Publication Patent No. 1999-0034085 discloses a method for preparing a cellophane substitute film using carrageenan raw polymers and a composition thereof, and Korean Authorized Patent No. 1770227 discloses a method for preparing an antifouling-moisture-proof barrier coating composition and a method for preparing an antifouling-moisture-proof barrier film using the same. However, a barrier coating method using the biodegradable seaweed fiber of the present invention, a barrier sheet including seaweed fibers, and a barrier paper coated with seaweed fibers have not been disclosed so far. Summary of the invention

[0006] Technical issues

[0007] The present invention is derived based on the above requirements, and its purpose is to provide barrier red algae fiber with oxygen permeation prevention characteristics and excellent dehydration effect during the coating process, its preparation method, barrier coated paper and barrier sheet including the same.

[0008] Solutions to the problem

[0009] In order to solve the above-mentioned problems, the present invention provides barrier red algae fibers including elliptical red algae fibers having a major axis length of 50 to 500 μm in cross section.

[0010] According to an embodiment of the present invention, the fiber wall thickness of the elliptical red algae fiber may be 50-500 nm.

[0011] Furthermore, the oval red algae fibers may account for more than 50 weight percent of the total weight of the barrier red algae fibers.

[0012] Furthermore, the barrier red algae fiber is formed by red algae, and the red algae include one or more of Eucheuma cottonii, Eucheuma spinosum and Gracilaria.

[0013] Furthermore, the present invention provides a method for preparing barrier red algae fiber, which comprises: step (1), adding 1000-3000 parts by weight of water to 100 parts by weight of a mixture of 0.1-5.0 parts by weight of sulfuric acid and 95-99.9 parts by weight of red algae, reacting the mixture at 60-120° C. for 1-5 hours to remove carrageenan or agar, and obtaining remaining red algae residue; and step (2), adding 400-600 parts by weight of water and 0.5-5.0 parts by weight of a bleaching substance to 100 parts by weight of the red algae residue obtained in the above step (1), adjusting the pH to 3-5, and reacting the mixture at 60-95° C. for 0.5-5 hours to bleach and wash the red algae residue to obtain barrier red algae fiber.

[0014] According to an embodiment of the present invention, the bleaching substance may be one or more of chlorine dioxide, sodium hypochlorite, chlorine, ozone and oxygen.

[0015] Furthermore, the present invention provides a barrier coated paper comprising paper and a barrier coating layer coated on at least a portion of the surface of the paper, comprising the barrier red algae fiber.

[0016] According to an embodiment of the present invention, the barrier coating layer may further include a polymer. The barrier coating layer may include 10 to 99 weight percent of the polymer and 1 to 90 weight percent of the barrier red algae fiber.

[0017] Furthermore, the polymer may include one or more selected from polyvinyl alcohol (PVA), starch, nanocellulose, chitin, poly-L-lactic acid (PLLA), stereo complex polylactic acid (sc-PLA), poly-(3-hydroxybuthyrate) (PHB), polybutylene succinate (PBS), polycaprolactone (PC A) and polyglycolic acid (PGA).

[0018] Furthermore, the weight of the barrier coating layer may be 1 to 100 g / m 2 .

[0019] Furthermore, the barrier coating layer may further include one or more of poly(amidoamine) (PAM), a wet strength agent and a hydrophobic agent.

[0020] Furthermore, the wet strength agent may include one or more of epoxy emulsion and epichlorohydrin, and the hydrophobic agent may include one or more of alkyl ketene dimer (AKD), alkenyl succinic acid (ASA) and rosin.

[0021] Furthermore, the present invention provides a barrier sheet comprising the barrier red algae fibers.

[0022] Effects of the Invention

[0023] The present invention is derived based on the above requirements. According to the barrier red algae fiber, its preparation method, barrier coated paper and barrier sheet including the same, the barrier red algae fiber of the present invention have better oxygen permeation resistance and dehydration performance during the coating process than the conventional nanocellulose derived from wood. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A flow chart showing the biodegradable barrier coating method of the present invention.

[0025] Figure 2 The electron microscope photograph of Eucheuma fiber (A), the result of confirming the thickness of Eucheuma fiber by atomic force microscope (B), and cylindrical nanocellulose of wood cellulose (C), A represents the thickness of the fiber with two fiber walls of about 100 nm overlapping, that is, 200 nm, B represents the surface height of the sample holder, and C represents that the wood cellulose is cylindrical, not elliptical, and the width of the original fiber reaches about 100 nm.

[0026] Figure 3 Comparison of Eucheuma fiber and cellulose fiber. (a) shows the XRD patterns of Eucheuma fiber and cellulose (softwood fiber), which is bleached pulp of coniferous trees. (b) is the HPLC result of analyzing the sugar (fructose, glucose and xylose) content of Eucheuma fiber and cellulose. DETAILED DESCRIPTION

[0027] The embodiments of the present invention are described in detail with reference to the accompanying drawings, so that those skilled in the art can easily implement the present invention. The present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. In the drawings, parts not related to the description are omitted in order to clearly illustrate the present invention. In the entire specification, the same or similar structural elements are marked with the same figure numbers.

[0028] The barrier red algae fibers according to the present invention include oval red algae fibers.

[0029] At this time, if Figure 2 As shown, the above-mentioned elliptical red algae fiber has an elliptical shape.

[0030] Furthermore, the major axis length of the cross section of the elliptical red algae fiber is 50 to 500 μm, preferably, the major axis length of the cross section can be 60 to 450 μm. When the major axis length of the cross section of the elliptical red algae fiber is less than 50 μm, the dehydration property may be reduced during the coating process, and when the major axis length of the cross section of the elliptical red algae fiber is greater than 500 μm, the oxygen permeation resistance may be reduced.

[0031] On the other hand, the term "major axis" as used in the present invention refers to an axis having the longest length in a cross section.

[0032] Furthermore, the fiber wall thickness of the oval red algae fiber may be 50 to 500 nm, preferably, the fiber wall thickness may be 60 to 450 nm. When the fiber wall thickness of the oval red algae fiber is less than 50 nm, the dehydration property may be reduced during the coating process, and when the fiber wall thickness of the oval red algae fiber is greater than 500 nm, the oxygen permeation resistance may be reduced.

[0033] Furthermore, the oval red algae fibers may account for 50 weight percent or more of the total weight of the barrier red algae fibers, preferably, 60 weight percent or more of the total weight of the barrier red algae fibers, and more preferably, 70 weight percent or more of the total weight of the barrier red algae fibers. When the oval red algae fibers account for less than 50 weight percent of the total weight of the barrier red algae fibers, the oxygen permeation resistance and the dehydration performance during the coating process may be reduced.

[0034] Furthermore, the barrier red algae fiber according to the present invention is prepared by steps (1) and (2).

[0035] Step (1) is to add 1000 to 3000 parts by weight of water to 100 parts by weight of a mixture of 0.1 to 5.0 weight percent of sulfuric acid and 95 to 99.9 weight percent of red algae, and react the mixture at 60 to 120° C. for 1 to 5 hours to remove carrageenan or agar to obtain a remaining red algae residue.

[0036] Step (2), adding 400 to 600 parts by weight of water and 0.5 to 5.0 parts by weight of a bleaching substance to 100 parts by weight of the red algae residue obtained in the above step (1), adjusting the pH to 3 to 5, and reacting the mixture at 60 to 95° C. for 0.5 to 5 hours to bleach and clean the red algae residue to obtain barrier red algae fiber.

[0037] At this time, the red algae preferably includes one or more of Eucheuma cottonii, Eucheuma spinosum and Gracilaria, but is not limited thereto.

[0038] Furthermore, the bleaching substance is preferably one of chlorine dioxide, sodium hypochlorite, chlorine, ozone and oxygen, more preferably chlorine dioxide or sodium hypochlorite, and further preferably chlorine dioxide, which is more conducive to achieving the purpose of the present invention.

[0039] Furthermore, the present invention provides a barrier coated paper comprising paper and a barrier coating layer coated on at least a portion of the surface of the paper, comprising the barrier red algae fiber.

[0040] At this time, the barrier coating layer may further include a polymer, and the barrier coating layer may include 10 to 99 weight percent of the polymer and 1 to 90 weight percent of the barrier red algae fiber. The polymer and the barrier red algae fiber satisfy the above content range, which is more conducive to achieving the purpose of the present invention.

[0041] The above-mentioned polymer preferably includes one or more selected from polyvinyl alcohol (PVA), starch, nanocellulose, chitin, poly-L-lactic acid (PLLA), stereocomplex polylactic acid (sc-PLA), poly-(3-hydroxybutyrate) (PHB), poly-(3-hydroxy buthyrate) (PBS), polybutylene succinate (PCA), polycaprolactone (PCA) and polyglycolic acid (PGA), but is not limited thereto.

[0042] On the other hand, the barrier coating layer can be formed by mixing the polymer and the barrier red algae fiber and coating the mixture on the surface of paper.

[0043] In this case, before mixing the polymer and the barrier red algae fiber, hydrogen peroxide and the barrier red algae fiber may be mixed, and after adjusting the pH, heat treatment may be performed to perform secondary bleaching.

[0044] At this time, the secondary bleaching can be performed by mixing 0.5-5.0 weight percent of the hydrogen peroxide and 95-99.5 weight percent of the barrier red algae fiber, the pH can be adjusted to pH 10-13, and the heat treatment can be performed at a temperature of 60-95° C. for 0.5-5 hours.

[0045] On the other hand, the weight of the barrier coating layer can be 1 to 100 g / m 2 .

[0046] In addition, the barrier coating layer may further include one or more of poly(amidoamine) (PAM), a wet strength agent and a hydrophobic agent. The wet strength agent may include one or more of epoxy emulsion and epichlorohydrin, and the hydrophobic agent may include one or more of alkyl ketene dimer (AKD), alkenylsuccinic acid (ASA) and rosin, but is not limited thereto.

[0047] In another aspect, the present invention provides a barrier sheet comprising the barrier red algae fibers.

[0048] The barrier coating layer may be formed solely of the barrier red algae fibers, or may include a predetermined polymer and the barrier red algae fibers.

[0049] According to one embodiment of the present invention, the barrier sheet may further include a polymer. In this case, the barrier sheet may include 10 to 99 weight percent of the polymer and 1 to 90 weight percent of the barrier red algae fiber. The polymer and the barrier red algae fiber satisfy the above content range, which is more conducive to achieving the purpose of the present invention.

[0050] The above-mentioned polymer preferably includes one or more selected from polyvinyl alcohol (PVA), starch, nanocellulose, chitin, poly-L-lactic acid (PLLA), stereocomplex polylactic acid (sc-PLA), poly-(3-hydroxybutyrate) (PHB), poly-(3-hydroxy buthyrate) (PBS), polybutylene succinate (PCA), polycaprolactone (PCA) and polyglycolic acid (PGA), but is not limited thereto.

[0051] On the other hand, before mixing the polymer and the barrier red algae fiber, hydrogen peroxide and the barrier red algae fiber may be mixed, and after adjusting the pH, heat treatment may be performed to perform secondary bleaching.

[0052] At this time, the secondary bleaching can be performed by mixing 0.5-5.0 weight percent of the hydrogen peroxide and 95-99.5 weight percent of the barrier red algae fiber, the pH can be adjusted to pH 10-13, and the heat treatment can be performed at a temperature of 60-95° C. for 0.5-5 hours.

[0053] On the other hand, the gram weight of the barrier sheet can be 1 to 100 g / m 2 .

[0054] In addition, the barrier sheet may further include one or more of poly(amidoamine) (PAM), a wet strength agent and a hydrophobic agent. The wet strength agent may include one or more of epoxy emulsion and epichlorohydrin, and the hydrophobic agent may include one or more of alkyl ketene dimer (AKD), alkenyl succinic acid (ASA) and rosin, but is not limited thereto.

[0055] The present invention will be described in more detail below using examples. These examples are only used to more specifically illustrate the present invention, and the scope of the present invention is not limited to these, which is obvious to those skilled in the art.

[0056] Example

[0057] Example 1-1. Preparation of barrier red algae fiber (Eucheuma cottonii fiber)

[0058] Use basis Figure 1The preparation method disclosed in the flowchart is used to prepare Eucheuma fiber (barrier red algae fiber).

[0059] a. After adding 300 g of dried Eucheuma odoratum as red algae fiber to 6000 g of water to make a weight ratio of 20:1 (water: Eucheuma odoratum), 0.3 weight percent of sulfuric acid was added as the weight ratio of Eucheuma odoratum. Then, the temperature was raised for 30 minutes, and the mixture was reacted at 100°C for 3 hours. Carrageenan was fully extracted using a 200-mesh sieve, and the remaining residue was referred to as "Eucheuma odoratum residue (red algae residue)".

[0060] b. After the weight ratio of water to Eucheuma residue was adjusted to 5:1, 2 weight percent of chlorine dioxide was added to the dry weight of Eucheuma residue, and the pH was adjusted to 3.5 with acetic acid. Then, the Eucheuma residue was bleached by reacting at 90°C for 1 hour and 30 minutes, and the washed product was called "Eucheuma fiber (barrier red algae fiber)".

[0061] In Example 1 of the present invention, it can be confirmed from the XRD results and sugar analysis results of the Eucheuma fiber that the Eucheuma fiber is composed of cellulose ( Figure 3 ), after extracting agar from Gracilaria, "cellulose fibers" can also be obtained from the remaining solid components.

[0062] The prepared barrier red algae fibers include 80 weight percent of elliptical red algae fibers whose major axis length of the cross section satisfies 50-500 μm and whose fiber wall thickness satisfies 50-500 nm.

[0063] Example 1-2

[0064] The barrier red algae fibers were prepared in the same manner as in Example 1-1, except that Eucheuma auris was replaced with Gracilaria spp. The barrier red algae fibers prepared included 70 weight percent of elliptical red algae fibers having a major axis length of 50 to 500 μm and a fiber wall thickness of 50 to 500 nm.

[0065] Comparative Example 2-1

[0066] The same method as in Example 1-1 was used to prepare the barrier red algae fibers, except that the red algae Eucheuma odoratum was replaced with the red algae Gelidium amansoniae. The barrier red algae fibers were cylindrical fibers with a major axis length of 500 to 800 μm and a fiber thickness of 1000 to 2200 nm.

[0067] Comparative Example 2-2

[0068] Nanocellulose was prepared by passing hardwood bleached pulp through a super mass colloidor 60 times at a concentration of 1.5%. The obtained nanocellulose was cylindrical fiber with a major axis of 8.2 μm and a fiber width of 35.2 nm.

[0069] Preparation Examples 1-1 to 1-2 and Comparative Preparation Examples 1-1 to 1-2. Preparation of Barrier Sheets

[0070] The fibers prepared in Example 1-1, Example 1-2, Comparative Example 2-1 and Comparative Example 1-2 were used to prepare a 10 g / m2 filter on a cellulose acetate membrane (0.45 μm pore size, H YUNDAI MICRO, Republic of Korea) filter. 2 Barrier sheet.

[0071] Experimental Example 1: Oxygen Permeability (OP) and Permeability Analysis

[0072] The oxygen permeability of the barrier sheets prepared in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-2 was measured. The oxygen transmission rate was measured using an ultra-precision oxygen analyzer (OX-TRAN Model 2, MOCON, USA) at 23 degrees Celsius, 1 atmosphere, and 0 relative humidity for 24 hours. In order to correct the thickness of the barrier sheet, the oxygen permeability was calculated by dividing the oxygen permeability by the sheet thickness.

[0073] Furthermore, the cellulose acetate membrane (0.45 μm pore size, HYUNDAI M ICRO, Republic of Korea) was used to filter the sample with a grammage of 5 g / m 2 The dehydration property was analyzed by measuring the time required for the barrier sheets to stop dehydration when the same vacuum pressure was applied.

[0074] The results are shown in Table 1 below.

[0075] Table 1

[0076]

[0077] As shown in Table 1 above, it can be confirmed that Preparation Example 1-1 and Preparation Example 1-2, which all meet the long axis length, fiber wall thickness and content of the elliptical red algae fiber of the present invention, have significantly lower oxygen permeability than Comparative Preparation Example 1-1 which exceeds the long axis length and fiber wall thickness range of the cross-section and uses cylindrical fibers, and have significantly faster dehydration time than Comparative Preparation Example 1-2 which is less than the long axis length and fiber wall thickness range of the cross-section and uses cylindrical fibers.

[0078] Preparation Example 2: 5 g of Eucheuma fiber was coated on the coated base paper.

[0079] After mixing 60 weight percent of Eucheuma fiber prepared in Example 1-1 and 40 weight percent of PVA (polyvinyl alcohol), a coated base paper (coated base paper purchased from M Paper Company in South Korea with a gram weight of 50 g / m 2 The base paper (hereinafter referred to as "coated base paper") is coated with a coating strip so that the weight of the coating layer is 5 g per square meter on a dry weight basis, and the base paper is dried.

[0080] Preparation Example 3: 10 g of Eucheuma fiber was coated on the coated base paper.

[0081] After mixing 60 weight percent of Eucheuma fiber prepared in Example 1-1 and 40 weight percent of PVA (polyvinyl alcohol), the mixture was coated on a coating base paper using a coating strip so that the weight of the coating layer was 10 g per square meter on a dry weight basis, and then dried.

[0082] Comparative Preparation Example 2. Preparation of Barrier Sheet of Bleached Hardwood Pulp 1

[0083] The bleached hardwood pulp was beaten with a Valley beater to a freeness of 510 ml according to Canadian standard, and a barrier sheet weighing 20 g / m2 was prepared in the same manner as in Preparation Example 1-1.

[0084] Comparative Preparation Example 3. Preparation of Barrier Sheet of Bleached Hardwood Pulp 2

[0085] The bleached hardwood pulp was beaten with a Valley beater to a freeness of 95 ml according to Canadian standard, and a barrier sheet weighing 20 g / m2 was prepared in the same manner as in Preparation Example 1-1.

[0086] Comparative Preparation Example 4. Preparation of Microfibrils and Nanocellulose

[0087] The beaten hardwood fiber of Comparative Preparation Example 3 was used and repeatedly beaten 20 times using a supermass colloidor to prepare cylindrical microfibrils (CMF) having a fibril length of 25.5 μm and a fibril width of 185 nm on average.

[0088] Furthermore, the beaten hardwood fibers of Comparative Preparation Example 3 were repeatedly beaten 60 times using a supermass colloidor to prepare cylindrical cellulose nano-fibrils (CNF) having a fibril length of 7.6 μm and a fibril width of 45 nm on average.

[0089] Comparative Preparation Example 5. Preparation of 10g / m2 barrier sheet using CMF

[0090] The CMF prepared in Comparative Preparation Example 4 was used to prepare a barrier sheet of 10 g / m2 on a nanofilter.

[0091] Comparative Preparation Example 6. Preparation of 10g / m2 Barrier Sheet Using CNF

[0092] A barrier sheet of 10 g / m2 was prepared on a nanofilter using the CNF prepared in Comparative Preparation Example 4.

[0093] Comparative Preparation Example 7. Coating CMF 10g on coated base paper

[0094] After mixing 60 weight percent of the dry CMF prepared in Comparative Preparation Example 4 and 40 weight percent of PVA (polyvinyl alcohol), the mixture was coated on the coating base paper using a coating bar so that the weight of the coating layer was 10 g per square meter on a dry weight basis, and then dried.

[0095] Comparative Preparation Example 8: Coating CNF 10g on Coated Base Paper

[0096] After mixing 60 weight percent of the dry CNF prepared in Comparative Preparation Example 4 and 40 weight percent of PVA (polyvinyl alcohol), the mixture was coated on a coating base paper using a coating bar so that the weight of the coating layer was 10 g per square meter on a dry weight basis, and then dried.

[0097] Comparative Preparation Example 9. Membrane Preparation

[0098] After heating PLA (1.2-1.6% stereoisomer of D-isomer lactide (PLA-4032D) and average molecular weight of 220 kDa) at 160-180° C. in an extruder (Multi-Layer T-die Extrusion Film Production Line, Hankook EM, Korea), a film of 10 g / m2 was prepared.

[0099] Comparative Preparation Example 10. Coated Base Paper

[0100] Coated base paper weighing 50 g / m2 was purchased from M Company in Korea.

[0101] Experimental Example 2. Oxygen permeability (OP) analysis

[0102] The composition components of the above-mentioned Preparation Examples 1-1, 2, 3 and Comparative Preparation Examples 2 to 10 and their oxygen permeabilities were measured (measured by the oxygen permeability measurement method of Experimental Example 1).

[0103] Table 2 shows the results of oxygen permeability (OP) of the films. Considering that polyvinylidene chloride (PVDC) is a polymer barrier film with excellent oxygen permeability, the oxygen permeability is 10 to 300 cm 3 μm / m 2 ·day·atm, it was judged that the ear-shaped silk fiber (Preparation Example 1-1) and CNF (Comparative Preparation Example 6) as biodegradable substances can play a very good oxygen barrier role. In comparison, it was confirmed that the barrier sheets of hardwood fiber (Comparative Preparation Example 2, Comparative Preparation Example 3) and PLA (Comparative Preparation Example 9) that were subjected to more pulping had very high oxygen permeability, and CMF (Comparative Preparation Example 5) also did not play an excellent barrier role.

[0104] Table 2

[0105] Oxygen permeability of barrier sheets or films

[0106]

[0107]

[0108] Table 3 confirms that when 10g / m 2When Eucheuma fiber (Preparation Example 3) and CNF are coated on the coated base paper (Comparative Preparation Example 8), they can play an excellent oxygen barrier role like PVDC film. However, when a small amount of Eucheuma fiber is coated, it shows an oxygen permeability slightly higher than PVDC as in Preparation Example 2. In contrast, CMF (Comparative Preparation Example 7) still shows an oxygen permeability significantly higher than PVDC.

[0109] Table 3

[0110] Oxygen permeability after coating on 50g / m2 coated base paper

[0111]

[0112] As described above, it was confirmed that Eucheuma fiber and CNF can play an excellent oxygen barrier role. However, in order to prepare CNF, it is necessary to prepare bleached wood pulp first, and in order to prepare nanocellulose, a lot of energy is required. In contrast, Eucheuma fiber can be prepared only through a simple bleaching process, which has the advantage of requiring less energy.

[0113] Experimental Example 3. Dehydration Analysis

[0114] In order to apply biodegradable films or coating materials as packaging materials, water needs to be used as a medium. When the dehydration rate of the water used as the medium is delayed, the production rate of preparing the film becomes slow, and it is difficult to apply at a high concentration during coating. Therefore, it is necessary to confirm whether the dehydration property is excellent.

[0115] The dehydration test was performed by filtering the sample on a cellulose acetate membrane (0.45 μm pore size, HYUNDAI MICRO, Republic of Korea) with a grammage of 5 g / m 2 The time required for the barrier sheet to no longer be dehydrated when the same vacuum pressure is applied is measured.

[0116] The results of the dehydration analysis are shown in Table 4. CMF (Comparative Preparation Example 5) or CNF (Comparative Preparation Example 6) dehydrates very slowly. Unless special equipment or a lot of drying energy is used, the possibility that product production will inevitably be affected is very high.

[0117] On the contrary, it was confirmed that Eucheuma fiber has dewatering properties to the same extent as hardwood pulp subjected to heavy beating, and thus can be produced directly using a papermaking machine with high productivity and low drying energy.

[0118] Table 4

[0119] Dehydration characteristics of biodegradable barrier raw materials

[0120]

[0121] The above describes one embodiment of the present invention, but the concept of the present invention is not limited to the embodiment proposed in this specification. Ordinary technicians in the technical field of the present invention who understand the concept of the present invention can easily propose other embodiments within the scope of the same concept by adding, changing, deleting, and adding structural elements, but this also falls within the scope of the concept of the present invention.

Claims

1. A barrier red algae fiber, characterized in that: The invention comprises oval red algae fibers with a major axis length of 50 to 500 μm in cross section.

2. The barrier red algae fiber according to claim 1, characterized in that: The fiber wall thickness of the oval red algae fiber is 50 to 500 nm.

3. The barrier red algae fiber according to claim 1, characterized in that: The oval red algae fibers account for more than 50 weight percent of the total weight of the barrier red algae fibers.

4. The barrier red algae fiber according to claim 1, characterized in that: The barrier red algae fiber is formed by red algae, and the red algae include one or more of Eucheuma auriculata, Eucheuma spinulosa and Gracilaria spp.

5. A method for preparing barrier red algae fiber, characterized in that: include: Step (1), adding 1000 to 3000 parts by weight of water to 100 parts by weight of a mixture of 0.1 to 5.0 weight percent sulfuric acid and 95 to 99.9 weight percent red algae, reacting the mixture at 60 to 120° C. for 1 to 5 hours to remove carrageenan or agar to obtain a remaining red algae residue; as well as Step (2), adding 400 to 600 parts by weight of water and 0.5 to 5.0 parts by weight of a bleaching substance to 100 parts by weight of the red algae residue obtained in the above step (1), adjusting the pH to 3 to 5, and reacting the mixture at 60 to 95° C. for 0.5 to 5 hours to bleach and clean the red algae residue to obtain barrier red algae fiber.

6. The method for preparing barrier red algae fiber according to claim 5, characterized in that: The bleaching substance is one or more of chlorine dioxide, sodium hypochlorite, chlorine, ozone and oxygen.

7. A barrier coated paper, characterized in that: include: Paper; as well as The barrier coating layer is coated on at least a portion of the surface of the paper, and comprises the barrier red algae fiber according to any one of claims 1 to 4.

8. The barrier coated paper according to claim 7, characterized in that: The barrier coating layer also includes polymers, The barrier coating layer comprises 10 to 99 weight percent of the polymer and 1 to 90 weight percent of the barrier red algae fiber.

9. The barrier coated paper according to claim 8, characterized in that: The above-mentioned polymer includes one or more selected from polyvinyl alcohol (PVA), starch, nanocellulose, chitin, poly-L-lactic acid (PLLA), stereocomplex polylactic acid (sc-PLA), poly-(3-hydroxybutyrate) (P HB), polybutylene succinate (PBS), polycaprolactone (PCA) and polyglycolic acid (P GA).

10. The barrier coated paper according to claim 7, characterized in that: The weight of the barrier coating layer is 1 to 100 g / m 2 .

11. The barrier coated paper according to claim 7, characterized in that: The barrier coating layer further comprises one or more of poly(amidoamine) (PAM), a wet strength agent and a hydrophobic agent.

12. The barrier coated paper according to claim 11, characterized in that: The wet strength agent includes one or more of epoxy emulsion and epichlorohydrin, and the hydrophobic agent includes one or more of alkyl ketene dimer (AKD), alkenyl succinic acid (ASA) and rosin.

13. A barrier sheet, characterized in that: The invention comprises the barrier red algae fiber according to any one of claims 1 to 4.